Clinical utility of ixekizumab in the treatment of moderate-to-severe plaque psoriasis - Sekhon, Sahil (Psoriasis (Auckl), 2017)
Psoriasis vulgaris is a chronic, immune-mediated systemic disease that affectŝ7.5 million people in the US. It can be treated with many therapies, often in combination, which include topicals, phototherapy, oral systemics, and biologics. Biologic agents target specific components of the immune system involved in the pathogenesis of psoriasis including TNF-alpha, IL-12, IL-17, and IL-23. The biologic ixekizumab, approved for the treatment of moderate–severe plaque psoriasis in the US, targets IL-17. This review describes the role of IL-17 in psoriasis, the mechanism by which ixekizumab targets this cytokine, and the clinical utility of ixekizumab.